PEMBERDAYAAN EKONOMI KELUARGA MELALUI PELATIHAN KEWIRAUSAHAAN UNTUK WALI SISWA MTS. NEGERI 1 SERANG - Rustandi, Tata; Samsinar, Ade; Permatasari, Diah; Amyati, Amyati; Husni, Mohamad (Indonesian Collaboration Journal of Community Services (ICJCS), 2024)
Entrepreneurship training for guardians of students at MTs. Negeri 1 Serang aims to strengthen the family economy through increasing knowledge and skills in entrepreneurship. This activity was carried out on May 11 2024 involving active participation from participants. The structured and systematic implementation method includes theory and practical sessions to provide an in-depth understanding of the concepts of entrepreneurship, business management and marketing. Participant evaluations showed a significant increase in entrepreneurial understanding and skills after attending the training. Apart from that, this activity also facilitates the formation of networks and collaboration between participants, which is expected to provide continuous support in developing their businesses. Planned follow-up will be carried out to ensure that the positive impact of this training is sustainable in the long term